Identification and characterization of decision-making factors over industrial energy efficiency measures in electric motor systems. (October 2021) - Accordini, D.; Cagno, E.; Trianni, A.
Abstract: Energy efficiency measures in electric motor systems are scarcely implemented and previous literature has largely overlooked the characterizing factors responsible for their adoption in industrial operations. The present study, after a comprehensive literature review, aims at supporting research by offering a framework for the identification of the factors that should be assessed when considering the adoption of electric motor systems' energy efficiency measures. The proposed factors are clustered in ten categories, namely: contextual factors, compatibility, economy, energy savings, production-related factors, operations-related factors, synergies, complexity, personnel and additional technical factors. After a preliminary empirical validation, the proposed framework has been applied in a selected sample of manufacturing firms. Findings show that factors more closely related to the firm's production and operations result most critical for the adoption of energy efficiency measures. However, the adoption process is also deeply influenced by their complexity or compatibility to the specific context application, therefore calling for an exhaustive assessment. The adoption of the framework would have reversed some firm's decisions over the initial uptake of energy efficiency measures that proved to have critical issues for their implementation. Therefore, the proposed framework provides additional support and further value to decision-makers especially for non-energy intensive firms, where the impact on non-energy production resources becomes more important, and small-medium enterprises usually present greater difficulties for a holistic assessment of energy efficiency measures. The study concludes with main implications for research and policy-making from the present study as well as suggestions for future research. Highlights: Novel framework of characterizing factors for electric motor systems in industry. Thorough assessment of energy efficiency measures in electric motor systems. Decision-making factors for the adoption of energy efficiency measures. Impacts of energy efficiency on firms' production resources and operations.